2022
DOI: 10.3390/su14052586
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effective Solution for Non-Convex Economic Load Dispatch Problems in Power Systems Using Slime Mould Algorithm

Abstract: Slime Mould Algorithm (SMA) is a newly designed meat-heuristic search that mimics the nature of slime mould during the oscillation phase. This is demonstrated in a unique mathematical formulation that utilizes adjustable weights to influence the sequence of both negative and positive propagation waves to develop a method to link food supply with intensive exploration capacity and exploitation affinity. The study shows the usage of the SM algorithm to solve a non-convex and cost-effective Load Dispatch Problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…Researchers have applied the slime mould algorithm and its variants to engineering optimization problems and other research fields. For example, solving single- and du-al-objective economic and emission scheduling (EED) problems considering valve point effects [ 34 ]; determining the best operating rules for complex hydropower multi-reservoir prediction problems [ 38 ]; distributed generation (DG) solution of distribution network reconfiguration (DNR) problem [ 39 ]; photovoltaic model optimization design (Lin, 2022); demand estimation of urban water resources problem [ 40 ]; feature selection [ 41 ]; Reliability optimization of micro-milling cutting parameters [ 42 ]; Opti-mal Power Flow Problem [ 43 ]; A Cost-Effective Solution for Non-Convex Economic Load Dispatch Problems in Power Systems [ 44 ]; path planning and obstacle avoidance problem in mobile robots [ 45 ], optimal load-shedding in distribution system problem [ 30 ], etc.…”
Section: Related Workmentioning
confidence: 99%
“…Researchers have applied the slime mould algorithm and its variants to engineering optimization problems and other research fields. For example, solving single- and du-al-objective economic and emission scheduling (EED) problems considering valve point effects [ 34 ]; determining the best operating rules for complex hydropower multi-reservoir prediction problems [ 38 ]; distributed generation (DG) solution of distribution network reconfiguration (DNR) problem [ 39 ]; photovoltaic model optimization design (Lin, 2022); demand estimation of urban water resources problem [ 40 ]; feature selection [ 41 ]; Reliability optimization of micro-milling cutting parameters [ 42 ]; Opti-mal Power Flow Problem [ 43 ]; A Cost-Effective Solution for Non-Convex Economic Load Dispatch Problems in Power Systems [ 44 ]; path planning and obstacle avoidance problem in mobile robots [ 45 ], optimal load-shedding in distribution system problem [ 30 ], etc.…”
Section: Related Workmentioning
confidence: 99%
“…In [25], authors have used a data mining-based approach for solving multi-objective ELD. In [26], authors have used nonconvex ELD problem by Slime Mould Algorithm (SMA). In [27], authors have proposed an adaptive version of Class Topper Optimization (CTO) along with the incorporation of chaos theory for solving ELD, EED, and CEED.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal power flow and economic dispatch (ED) seem to be crucial minimization aspects in power systems that necessitate efficient generator interoperability, strategic planning, and scheduling [2]. In [3], a slime mould technique driven by customizable weight vector to control the series among positive and negative propagation waves was utilized for the minimized ED problem. In [4], a bi-stage self-adaptive differential evolution (DE) approach of k-nearest neighbours relying computation system has been designed to address numerous metaheuristic issues, and it was suggested that the ED problem be addressed in the upcoming years.…”
Section: Introductionmentioning
confidence: 99%